2000
DOI: 10.1007/s11837-000-0109-x
|View full text |Cite
|
Sign up to set email alerts
|

Alloy design strategies for promoting protective oxide-scale formation

Abstract: Figure 1. A scanning electron microscopy (backscatter mode) cross-section micrograph of Nb-33Ti-40Al (in at.%) after 15 minutes at 1,400°C in air. The continuous Al 2 O 3 scale cuts off the formation of more rapidly growing niobium-rich transient oxides. 3 5 µm with the thermochemistry of the environment and the temperature of the reaction. Oxidation can lead to a loss of load-bearing capacity in a component by the reduction of metallic cross section and, for many high-temperature applications, is the primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(122 citation statements)
references
References 57 publications
(50 reference statements)
3
118
0
1
Order By: Relevance
“…Effect of Ag and Cr addition on the oxidation behavior of two phase α2-Ti3Al + γ-TiAl in TiAl based alloys have been investigated 34 . These two alloying elements were expected to have reservoir-effect that supports the formation of continuous stable Al2O3 scale as reported previously in single phase TiAl intermetallic compounds 35,36,37 . In this alloy systems, chromium can act as Laves phase-Ti(Cr,Al)2 stabilizer while silver stabilizes Z phase-Ti5Al3O2.…”
Section: Oxidation Of 2-ti3al/ -Tial Alloyssupporting
confidence: 78%
See 1 more Smart Citation
“…Effect of Ag and Cr addition on the oxidation behavior of two phase α2-Ti3Al + γ-TiAl in TiAl based alloys have been investigated 34 . These two alloying elements were expected to have reservoir-effect that supports the formation of continuous stable Al2O3 scale as reported previously in single phase TiAl intermetallic compounds 35,36,37 . In this alloy systems, chromium can act as Laves phase-Ti(Cr,Al)2 stabilizer while silver stabilizes Z phase-Ti5Al3O2.…”
Section: Oxidation Of 2-ti3al/ -Tial Alloyssupporting
confidence: 78%
“…In the middle, intermixed of majorly TiN and minor of TiO2 and Al2O3 were formed. This TiO2 occurred when some TiN oxidized 36 . Longer times as well as higher oxidation temperatures might change the scale compositions.…”
Section: Oxidation Of 2-ti3al/ -Tial Alloysmentioning
confidence: 99%
“…The oxidation resistance will depend on the ability of the alloys to form, and maintain, a compact and adherent scale that will protect the alloy from further oxidation attack. 1 Loss of the protective oxide scale becomes problematic as it exposes the parent alloy to further oxidation attack. Stresses in the oxide scale due to intrinsic growth stresses, thermal stresses, or externally applied stresses all increase the likelihood of scale failure.…”
Section: Introductionmentioning
confidence: 99%
“…These coatings change their structure and properties in response to various operating conditions [125][126][127][128]. (b) Smart coatings, which are functionally graded systems that may be characterized by the variation in composition and structure gradually over volume, resulting in corresponding changes in the properties depending on the stages of wear process [99,[129][130][131][132][133][134][135][136]. (c) Adaptive coatings that can change their structure and properties as a result of the engineered surface dynamic response to the environmental impact due to formation of surface tribofilms.…”
Section: Adaptive/smart Coatings: Previous Artmentioning
confidence: 99%
“…It was shown that addition of Cr to the TiAlN-based coating strongly promotes its oxidation resistance owing to favorable changes in electronic and crystal structure [63,252]. Many studies aimed to improve oxidation resistance of various heat-resistant metallurgical systems such as alloys based on MCrAl (M = Ni, Fe, Co) [253] or TiAl [132] by incorporating various foreign elements such as Y [68,[254][255][256], Hf, Nb, B [257,258], V [259] or Si [64,109,111,217,260,261]. Among these dopants, Si and Y seem to be the most promising for improving the oxidation resistance of hard nitride coatings at relatively small concentrations.…”
Section: Physicochemical Properties: Adaptive Nanostructured Coatingsmentioning
confidence: 99%